2016
DOI: 10.14400/jdc.2016.14.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Jobs and Gender in our age of convergence: Research on Male Nurses

Abstract: This research paper is of a 'mixed method' research design: the quantitative analysis covering general data and the current condition of male nurses, the qualitative analysis being used on interview transcript data. The research subjects are 19 male nurses who work at a hospital and 29 female nurses who are doing Masters degrees in "J" province of the Republic of Korea. The data collection period was March 25 to April 1, 2015. The quantitative data was analyzed with SPSS WIN 19.0 software while the qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Fifth, "strategy and support for survival" comprised "communicating with each other", "support of male colleagues", and "encouragement received from fellow and senior nurses". It is not easy for some men to work in a workplace in which women form the majority; therefore, many male nurses find it difficult to form personal relationships with female nurses [30,31]. Previous studies [7,18,32] suggested the use of meetings and outsidework activities to build relationships with colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, "strategy and support for survival" comprised "communicating with each other", "support of male colleagues", and "encouragement received from fellow and senior nurses". It is not easy for some men to work in a workplace in which women form the majority; therefore, many male nurses find it difficult to form personal relationships with female nurses [30,31]. Previous studies [7,18,32] suggested the use of meetings and outsidework activities to build relationships with colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo canadense mostra que enfermeiros docentes vivenciam preconceitos, discriminação de gênero e precisam se esforçar para conquistar autonomia e respeito (Zeb, Younas, Rasheed, Sundus, 2020). Pesquisa mostra que enfermeiros da Coreia do Sul têm uma visão positiva sobre a superação dos estereótipos tradicionais (Shin, Seo, Lee, 2016).…”
Section: Atuação Profissionalunclassified
“…Nurses who leave the clinical sector move to various fields, such as nursing education, public health, firefighting, industry, and community health promotion [10]. The transfer of male nurses to community organizations can help improve public awareness about male nurses [11]. Furthermore, despite posing another challenge, the migration of nurses to community organizations constitutes an opportunity to expand the nursing field and enhance professionalism [12,13].…”
Section: Introductionmentioning
confidence: 99%